A Systematic Literature Review of Trends, Challenges, and Impact of Innovation in Contemporary Enterprise and Entrepreneurship - Rianzah Munawaroh; Eni Noviani; Agung Winarno; Heny Kusdianti (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
This study is a Systematic Literature Review (SLR) to map the dynamics, challenges, and impacts of innovation, especially driven by digitalization in the contemporary enterprise and entrepreneurial ecosystem. This SLR is important because the existing literature is still fragmented and has not yet presented an integrated synthesis in the midst of a VUCA (Volatile, Uncertain, Complex, and Ambiguous) business environment. Using the PRISMA methodology, 15 key articles for the 2020-2025 period were analyzed in depth. The main results show that digital innovation and entrepreneurial competence are the main determinants of MSME performance and competitiveness. There is a strong positive relationship between innovation and business performance. Interestingly, the findings indicate that individual entrepreneurial competencies often have a more direct and significant impact on performance than the results of product innovation itself. Although digitalization provides opportunities for market expansion and efficiency, MSMEs still face serious challenges in the form of digital literacy limitations and financial constraints. Educational institutions are emphasized to have a vital role in building sustainable entrepreneurial and ethical attitudes. The theoretical implication is the need for more sophisticated models to differentiate innovation impact pathways. Meanwhile, its managerial implications encourage business actors to focus on process innovation and improve adaptive competencies in order to survive global uncertainty.